Can diffusion- and perfusion-weighted imaging alone accurately triage anterior circulation acute ischemic stroke patients to endovascular therapy?. (19th March 2018) - Wolman, Dylan N; Iv, Michael; Wintermark, Max; Zaharchuk, Gregory; Marks, Michael P; Do, Huy M; Dodd, Robert L; Albers, Gregory W; Lansberg, Maarten G; Heit, Jeremy J
Abstract : Background and purpose: Acute ischemic stroke (AIS) patients who benefit from endovascular treatment have a large vessel occlusion (LVO), small core infarction, and salvageable brain. We determined if diffusion-weighted imaging (DWI) and perfusion-weighted imaging (PWI) alone can correctly identify and localize anterior circulation LVO and accurately triage patients to endovascular thrombectomy (ET). Materials and methods: This retrospective cohort study included patients undergoing MRI for the evaluation of AIS symptoms. DWI and PWI images alone were anonymized and scored for cerebral infarction, LVO presence and LVO location, DWI-PWI mismatch, and ET candidacy. Readers were blinded to clinical data. The primary outcome measure was accurate ET triage. Secondary outcomes were detection of LVO and LVO location. Results: Two hundred and nineteen patients were included. Seventy-three patients (33%) underwent endovascular AIS treatment. Readers correctly and concordantly triaged 70 of 73 patients (96%) to ET (κ=0.938; P=0.855) and correctly excluded 143 of 146 patients (98%; P=0.942). DWI and PWI alone had a 95.9% sensitivity and a 98.4% specificity for accurate endovascular triage. LVO were accurately localized to the ICA/M1 segment in 65 of 68 patients (96%; κ=0.922; P=0.817) and the M2 segment in 18 of 20 patients (90%; κ=0.830; P=0.529). Conclusion: AIS patients with anterior circulation LVO are accurately identified using DWI and PWI alone, and LVO location may be correctly inferred from PWI. MRA omission may be considered to expedite AIS triage in hyperacute scenarios or may confidently supplant non-diagnostic or artifact-limited MRA.